2021
DOI: 10.3390/nu13061885
|View full text |Cite
|
Sign up to set email alerts
|

Human Milk Concentrations of Minerals, Essential and Toxic Trace Elements and Association with Selective Medical, Social, Demographic and Environmental Factors

Abstract: This study aims to quantify concentrations of minerals and trace elements in human milk (HM) and infant formula (IF) and evaluate associations with medical, social, environmental, and demographic variables. A prospective, case series study of 170 nursing mothers was made. HM samples were obtained from full-term (colostrum, intermediate and mature HM) and preterm (mature HM) mothers. Variables of interest were assessed by a questionnaire. For comparison, IF samples (n = 30) were analyzed in a cross-sectional st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 50 publications
2
11
0
Order By: Relevance
“…Tl levels have been detected in all the samples at very low concentrations, this toxic has been also found naturally in the environment, and therefore can contaminate water and food as well as it was reported in Spanish HM in higher concentrations than our study. [15] In agreement with other studies, the presence of As has been associated to residence in an urban area (higher availability of As in food, water, and air caused by industrial activities). The change of toxic elements concentrations in HM associated with COVID-19, maybe explained by the homeostatic equilibria with other essential elements that could interact with them, as previously reported in the literature.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Tl levels have been detected in all the samples at very low concentrations, this toxic has been also found naturally in the environment, and therefore can contaminate water and food as well as it was reported in Spanish HM in higher concentrations than our study. [15] In agreement with other studies, the presence of As has been associated to residence in an urban area (higher availability of As in food, water, and air caused by industrial activities). The change of toxic elements concentrations in HM associated with COVID-19, maybe explained by the homeostatic equilibria with other essential elements that could interact with them, as previously reported in the literature.…”
Section: Discussionsupporting
confidence: 91%
“…However, no differences were observed depending on COVID-19 symptomatology (asymptomatic vs symptomatic). Furthermore, we also identified toxic elements (Ni, V, Al, Tl, and As) in HM samples as reported by other studies [15,35] and, also, we reported their higher presence for first time in COVID-19 mothers. Higher levels of Tl (1.4-fold, p = 0.008) and As (1.3-fold, p = 0.031) were identified in COVID-19 mothers compared to prepandemic controls.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Zn concentration in pooled DBM is about half that in preterm milk in the US [ 21 ], whereas only minimal differences in concentrations of other trace elements have been reported between term and preterm human milk [ 34 ]. In order to verify that Zn levels in DBM were as low as expected from the literature [ 12 , 13 , 21 ], Zn concentration was measured in a convenience sample ( n = 11 separate aliquots) of pooled DBM collected soon after implementing the DBM program.…”
Section: Materials/subjects and Methodsmentioning
confidence: 99%
“…However, milk can transfer toxic elements from the mother to the baby via breastfeeding. The presence of these toxins does not necessarily cause health hazards in the infant, but since these hazards are biologically probable, they should be monitored 3 . The first stage of transmission of contaminants to the baby begins from the time of placement in the mother's womb and continues until breastfeeding 4 .…”
Section: Introductionmentioning
confidence: 99%